ANALISIS PENDIDIKAN KARAKTER ANAK USIA 5-6 TAHUN SENTRA RUANG BALOK DI TAMAN KANAK KANAK - Putri Clawson; Wulan Dwi Wahyuningsih (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
This study is entitled Analysis of Character Education for Children Aged 5-6 Years at Beam Space Centers in Kindergarten. This study aims to determine the Character Education of Children Aged 5-6 Years at the Beam Room Center TK Negeri Pembina 3 Pekanbaru. The subjects of this study were 3 children out of 16 children in the beam center. This research method is descriptive qualitative. Descriptive research is a method for investigating objects that cannot be measured with numbers or other measures that are descriptive. This research is located in the peaceful marpoyan cluster at Pekanbaru city. Based on the results of research that the authors do the methods used in data collection are Observation, Interview, and Declaration. The Data Analysis Techniques used are: Data Reduction, Data Presentation, and Drawing Conclusions. The results in this study indicate that how the Character Education of Children 5-6 Years Old Beam Center Center in TK Negeri Pembina 3 Pekanbaru. Regarding the Analysis of Character Education for Children Aged 5-6 Years at the Beam Space Center in Kindergarten, from the results of the descriptive qualitative research conclusions obtained in the application of the characters instilled by the teacher towards their students, (1) children can tolerate each other, (2) children can improve the discipline of fellow friends, (3) children can be honest with each other.